Utility of serum TNF-α, infliximab trough level, and antibody titers in inflammatory bowel disease - Pallagi-Kunstár, Éva (Baishideng Publishing Group Co., Limited, 2014)
AIM: To assess tumor necrosis factor-α (TNF-α), infliximab (IFX) concentrations, and antibodies against IFX molecules in patients with inflammatory bowel disease (IBD) who develop loss of response, side effects, or allergic reaction during anti TNF-α therapy. METHODS: Blood samples of 36 patients with response loss, side effects, or hypersensitivity to IFX therapy (Group I) and 31 patients in complete clinical remission (Group II) selected as a control group were collected to measure trough serum TNF-α level, IFX, and anti-IFX antibody (ATI) concentration. We examined the correlation between loss of response, the development of side effects or hypersensitivity, and serum TNF-α, IFX trough levels, and ATI concentrations. RESULTS: The serum TNF-α level was shown to be correlated with the presence of ATI; ATI positivity was significantly correlated with low trough levels of IFX. ATIs were detected in 25% of IBD patients with loss of response, side effects, or hypersensitivity, however no association was revealed between these patients and antibody positivity or lower serum IFX levels. Previous use of IFX correlated with the development of ATI, although concomitant immunosuppression did not have any impact on them. CONCLUSION: On the basis of the present study, we suggest that the simultaneous measurement of serum TNF-α level, serum anti TNF-α concentration, and antibodies against anti TNF-α may further help to optimize the therapy in critical situations.